Grasses as Food and Feed - Tadele, Zerihun (IntechOpen, 2018)
The grass or Poaceae family includes all cereal crops and forage grasses. Hence, they play a significant role in the economy of both the developed and developing world. Similar to other crop types, grasses are continuously challenged by a variety of environmental constraints. These constraints include a variety of biotic and abiotic stresses, and an enabling environment, which mainly refers to policy-related issues that affect productivity. In this book, the importance of selected cereal crops and grasses as well as associated constraints are presented. In addition, techniques proven to improve the productivity of these groups of crops are discussed. The techniques include variety development, soil and crop management practices, and biological control of fungal pathogens using different types of bacterial strains.